A rare case of emphysematous pyelonephritis: a case report - Ishwarbhai, Kanajariya Tushar; Bhadreshwara, Kamlesh A.; Parmar, Mohini (International Surgery Journal, 2024)
Emphysematous pyelonephritis is a rare, severe, acute necrotizing renal parenchymal and perirenal infection with formation of gas. Emphysematous pyelonephritis predominantly affects females with uncontrolled diabetes and obstruction of the urinary tract are the main predisposing factors and Escherichia coli is the most frequent causative pathogen. We reported a case of a 66 year old female patient who presented with diarrhoea, fever and breathlessness for 5 days. Patient was a known case of type-2 diabetes mellitus. On per abdominal examination, guarding and rigidity were not present. Urine examination shows plenty of pus cells. Patient was underwent for CECT, which was suggestive of changes of emphysematous pyelonephritis with pneumoretroperitoneum. Patient was taken for bilateral D-J stenting and right PCN diversion. Approximately 1500 ml toxic fluid was drained from right kidney and was sent for culture and sensitivity examination. Culture of fluid shows moderate growth of Escherichia coli.